Isolation and molecular identification of Nipah virus from pigs - Li, Yen Chang; Bakar, Sazaly Abu; S.H., Sharifah; Ali, A.R. Mohd; Yusoff, Khatijah; Zamrod, Zulkeflie (Penerbit Universiti Sains Malaysia, 2004)
An outbreak of febrile encephalitis with high death rates (~56%) occurred among pig farmers in a pig-farming community in Tambun, Perak, Malaysia, in 1998 (Wong et al., 2002). The disease spread southward within four to six months to several other pigfarming communities near or around Seremban, a city ~300 km from Tambun (Anonymous, 1999a). By April 1999, at least 85 deaths were reported in Seremban, 15 were recorded in Tambun (Anonymous, 1999b). All the cases from Tambun were recorded before the outbreak in Seremban. During the outbreaks, pigs in Seremban and Tambun manifested acute respiratory distress syndrome and encephalitis and subsequently died (Anonymous, 1999a; Anonymous, 1999b).